2006
DOI: 10.1121/1.4787647
|View full text |Cite
|
Sign up to set email alerts
|

Human response to low-intensity sonic booms heard indoors and outdoors

Abstract: A house on Edwards Air Force Base, CA, was exposed to low-intensity N-wave sonic booms during a 3-week test period in June 2006. The house was instrumented to measure the booms both inside and out. F-18 aircraft were flown to achieve a variety of boom overpressures from approximately 0.01 to 0.06 psf. During 4 test days, 77 test subjects heard the booms while seated inside and outside the house. Using the Magnitude Estimation methodology and artificial reference sounds, the subjects rated the annoyance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Sullivan gives a good synopsis of the history of sonic boom human response testing. 1 Recently, very small scale evaluations by "expert ears" have confirmed earlier studies 2 and suggested that single-event sonic boom noise levels not exceed 70-80 PLdB (outdoors) for viable community noise acceptance levels to support commercial supersonic aircraft over land. These levels are, by comparison to the Concorde and other supersonic military aircraft, quiet and are often referred to as "low booms."…”
Section: Introductionmentioning
confidence: 78%
“…Sullivan gives a good synopsis of the history of sonic boom human response testing. 1 Recently, very small scale evaluations by "expert ears" have confirmed earlier studies 2 and suggested that single-event sonic boom noise levels not exceed 70-80 PLdB (outdoors) for viable community noise acceptance levels to support commercial supersonic aircraft over land. These levels are, by comparison to the Concorde and other supersonic military aircraft, quiet and are often referred to as "low booms."…”
Section: Introductionmentioning
confidence: 78%
“…The A-weighted loudness has been found to correlate well with PLdB in the range of loudness levels pertinent to this paper. 13 The under-and off-track target ∆p/p ∞ are shown in Figs. 3(a) and 3(b), and the corresponding PLdB values for their ground signatures are 66 and 72, respectively.…”
Section: Generation Of Low-boom Targetsmentioning
confidence: 99%
“…7 The sonic booms heard on the ground are perceived by people as highly annoying noise. [8][9][10] This annoyance presents a major obstacle that prohibits overland supersonic flights. Perception studies suggest that both the perceived loudness and the annoyance of the sonic boom tend to increase with the increase of its peak overpressure and decrease of the shock rise time.…”
Section: Introductionmentioning
confidence: 99%